2003
DOI: 10.1021/ja037561l
|View full text |Cite
|
Sign up to set email alerts
|

In Situ TA-MS Study of the Six-Membered-Ring-Based Growth of Carbon Nanotubes with Benzene Precursor

Abstract: By using the in situ thermal analysis-mass spectroscopic technique, combined with transmission electron microscopic characterization of the carbon nanotube (CNT) product, we have studied the chemical vapor deposition (CVD) growth of CNTs with Fe-Co/gamma-Al2O3 catalyst and benzene precursor in the range of room temperature to 700 degrees C. The growth process has been clearly illuminated, which starts from the reduction of catalyst around 645 degrees C followed by the dissociation of carbon-hydrogen bonds of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 27 publications
6
49
0
Order By: Relevance
“…The authors have described a probable growth mechanism of CNTs from camphor in an earlier report 13 . Recently, a chinese group 22 carried out in-situ mass spectroscopy of benzene CVD and supported the ring-based CNT growth hypothesis reported by the present authors 13 .…”
Section: Resultssupporting
confidence: 85%
“…The authors have described a probable growth mechanism of CNTs from camphor in an earlier report 13 . Recently, a chinese group 22 carried out in-situ mass spectroscopy of benzene CVD and supported the ring-based CNT growth hypothesis reported by the present authors 13 .…”
Section: Resultssupporting
confidence: 85%
“…The reason for the formation of the conelike NWs can be explained according to the proposed growth mechanism below. Similar to the growth of carbon and CNx tubes by surface diffusion, [27][28][29][30] we speculate that, after the "Primary orientation growth" stage, growth by surface diffusion may also be part of the growth process (Figure 4f) axis. In addition, the surfaces of the cone-like In 2 O 3 NWs as shown in Figure 2c have some exiguous nanoparticles, which also support the surface diffusion mechanism.…”
Section: Formation Mechanismsupporting
confidence: 57%
“…Both share the common feature that they have hexagons as the building blocks. In fact, it has been reported that carbon nanotubes can be synthesized by directly using benzene molecules that, on dehydrogenation, leave hexagonal C 6 (25,26). When a nanotube is unzipped by catalysts, it becomes a graphene sheet.…”
mentioning
confidence: 99%